Parental Self-Efficacy to Promote Children’s Healthy Lifestyles: A Pilot and Feasibility Study - Cayetana Ruiz-Zaldibar (International Journal of Environmental Research and Public Health, 2021)
Positive parenting programs are a key strategy to promote the development of parental competence. We designed a pilot study based on parental self-efficacy to promote healthy lifestyles in their children aged between 2 to 5 years old. In this pilot study, we aimed to assess the effects of a parenting program on parental self-efficacy and parenting styles. Twenty-five parents were allocated into intervention (N = 15) and control group (N = 10). Parents from the intervention group received four group sessions (120 mi per session) to develop a positive parenting, parenting styles and parenting skills regarding to children’s diet, exercise, and screen time, and two additional sessions about child development and family games. Parents from the control group received these two latter sessions. Parental self-efficacy, parenting styles, and meal-related parenting practices were measured before and after the intervention and at 3-month follow-up. Acceptability and feasibility of the program was also measured. Quantitative data were analyzed using the repeat measures ANOVA and ANCOVA tests and the effect size calculation. Content analysis was used to analyse open questions. Positive trends were found regarding parental self-efficacy and the use of authoritative parenting style. Parents also reported a great acceptability of the program getting high satisfaction. According to the feasibility barriers and facilitators aspects were identified. The positive trends founded in this study support the development of parenting programs to promote healthy lifestyle in children.